THE IMPACT OF ARTIFICIAL INTELLIGENCE (AI) ON STUDENT CHARACTER DEVELOPMENT AT MADRASAH ALIYAH - Hamzah Irfanda; Wedra Aprison; Nurhasnah (BiCED Proceeding, 2024)
Along with the rapid development of artificial intelligence (AI) technology, its use has now penetrated the world of education, including in madrasah aliyah. AI has become an integral part of teaching and learning activities, both for completing assignments, finding references, and communicating online with teachers and fellow students. This phenomenon indicates that AI has the potential to facilitate access to information and accelerate academic work. However, behind these benefits, excessive use of AI can affect students' character building, especially in the aspects of responsibility, independence, and critical thinking skills. Therefore, this research is relevant to understand how much influence AI has on students' character development in madrasah aliyah. This research uses afield research with a qualitative approach. Data were collected through questionnaires or interviews, so the source of data came from respondents, namely individuals who answered the researcher's questions. Data analysis is carried out through the stages of data condensation, data presentation, and conclusion drawing. The use of artificial intelligence (AI) in learning has a mixed impact on students' character, especially in terms of decision-making skills, sense of responsibility, communication skills, ability to overcome difficulties, and self-confidence. Most students feel that AI helps them to speed up the learning process, improve efficiency, and provide references that enrich their knowledge. However, there are also concerns that over-reliance on ai may reduce their critical thinking, deep understanding, and social skills. Therefore, while AI can be a valuable support tool, the use of this technology needs to be accompanied by the awareness not to neglect the learning process that is fundamental and important in shaping students' character